A prefilter to improve the performance of transfer delay-based synchronization technique under distorted grid conditions. (December 2020) - Li, Jinbo; Wang, Qin; Xiao, Lan; Liu, Zehao; Wu, Qunfang; Liu, Zhihua
Abstract: The transfer delay-based adaptive frequency-locked loop (TD-AFLL) is a recently proposed synchronization technique. It has fast respond speed in ideal grid, but the performance degrades significantly in distorted grid. In this paper, a prefilter is proposed to enhance the robustness and harmonic rejection of the TD-AFLL. A fixed-coefficient bandpass filter (FCBF) is selected as the prefilter, which benefits from a simple structure and avoids the influence of frequency feedback dynamic of the TD-AFLL. Compare with standard TD-AFLL, the proposed FLL exhibits stronger harmonic rejection capability. Experimental results verify the effectiveness and advantages of the proposed technique.